Introduction: Entanglements of Anti-Feminism and Anti-Environmentalism in the Far-Right. Issue 110 (2nd October 2021) - Barla, Josef; Bjork-James, Sophie
ABSTRACT: This essay introduces the special issue of Australian Feminist Studies on 'Climate Change, Gender, and Authoritarianism: Entanglements of Anti-Feminism and Anti-Environmentalism in the Far-Right'. Starting from the hypothesis that anti-feminism functions as a metalanguage in the far-right's fight against liberal democracy as well as social and environmental justice, this special issue explores how anti-feminism and anti-environmentalism merge and inform one another in contemporary far-right discourses and politics on climate change. Focusing on the connections that form the tissue of far-right imaginaries of sex, gender, race, and the nation in the context of the simultaneous dismissal and mobilisation of ecological issues, a broad picture of the state of research on the entanglement of anti-feminism and anti-environmentalism in the far-right will be laid out. In doing so, this special issue aims at providing us with a much-needed insight into the gendered and racialised political ecology of the contemporary far-right.